Foraminíferos e tecamebas como indicadores ambientais em estuários tropicais - Brasil - Laut, Lazaro Luiz Mattos (2007)
Benthic foraminifera distribution has been a well reported in several coastal and estuarine regions in the world. Although each estuary shows individual characteristics that are the local result of tides, waves, winds, basin geomorphology, shelf morphology and other conditions that directly reflect in the foraminifera and thecamoebians assemblages composition. So, each estuary may have a particular assemblage that must be studied to make it possible to establish environmental models that can be used in paleoenvironmental reconstructions, and studies of environmental characterization and monitoring. Based on this principle, the aim of this study was the classification of seven estuaries from the Brazilian Coast, from North Cape to Santa Catarina Island (Araguari AP, Caeté PA, Potengi RN, Mataripe BA; Paraíba do Sul RJ, Suruí RJ e Itacorubí SC), using foraminifera and thecamoebians assemblages, associated to physical-chemical, sedimentological and microbiological parameters. Another goal pursued in this study, was the comparison of latitudinal distribution of species and assemblages, and their relationship with the characteristics used in the classification of sectors of the Brazilian tropical coast. Eighty-three foraminifera and twenty-three thecamoebians taxons were identified throughout the estuaries. The Pontengi (RN) Estuary showed the largest number of foraminifera taxons (43 species), and the Suruí presented the most thecamoebians (18 species). The most common foraminifera species throughout the estuaries were Arenoparrella mexicana and Haplophragmoides wilberti. On the other hand, Difflugia spp., Pontigulassia compressa, Cucurbitella corana and Cyclopyxis spp. were the most abundant thecamoebian species. It was not possible to identify a latitudinal restriction (1º N to 28º S) of species along the estuaries from the Brazilian coast. The absence of a given species in the estuary was related to local environmental conditions. In all of the studied estuaries the microbial activity showed a great influence on the organisms distribution. In the Northeastern estuaries, dominated by calcareous foraminifera, the diversity and richness indices decreased progressively related to bacterial biomass. In the Oriental and Southeastern Coasts, dominated by agglutinant foraminifera and thecamoebians, these indices increased gradually. This could be the result of different assemblages composition. The calcareous foraminifera showed negative correlation with sulphact-reduction bacteria. While the agglutinant foraminifera and thecamoebians had a positive correlation with this type of bacterial activity. The assemblages composition reflected the characteristics of each coastal segment. In the Northern coast two distinct macrotidal systems could be identified. The Araguari River, located in the macrocompartiment from Amapá coast, which is characterized as an erosive coast that receives a large load of suspended sediments from the Amazon River, was classified as a stratified estuary. It shows heterogeneity in the distribution of physical-chemical parameters, turbidity gradient and high diversity of thecamoebian species in the upper estuary, which decreases progressively towards the lower estuary, when they are replaced by agglutinant foraminifera. The Caeté River, located in the Macrocompartiment of Reentrâncias Pará-Maranhão, was classified as Non Stratified Macrotidal Estuary because it showed a homogeneous distribution of physical-chemical parameters, and foraminifera and thecamoebian assemblages. In the Northeast Coast, the two studied systems presented similarities in the species distribution and in the physical-chemical parameters. They were both classified as Stratified Mesotidal estuaries because of their high species diversity of calcareous foraminifera, that are replaced gradually by agglutinant foraminifera towards the upper estuary. The Paraíba do Sul River, located in the Macrocompartiment of Campos Basin, was classified as a Non-Stratified Microtidal Estuary for presenting a high thecamoebians species diversity throughout the system. The species of agglutinant foraminifera were found only next the river mouth. The presence of a large continental shelf with tons of suspended sediments inhibits the presence of calcareous species. In the Southeast coast it was possible to identify two different systems: the Suruí River, located in the Macrocompartiment of Sandy Cordões , dind t show an estuarine gradient, being classified as a Non-Stratified Microtidal Estuary; the Itacorubí Estuary is located in the Macrocompartiment of Coastal Plains from Santa Catarina, and was classified as Stratified Microtidal Estuary for presenting a species succession from lower estuary to upper estuary. The species zonation was a result of a narrow continental shelf that allows the arrival of truly marine species plus a small drainage basin. The methodology applied was efficient in the compartimentation and classification of estuarine systems from the Brazilian coast, and may be used as a foundation for environmental and paleoenvironmental studies.